Legal Review of Foundation Assets in Law No. 28 of 2004: Protection and Management of Foundation Assets - Aji, Ahmad Mukri; Yunus, Nur Rohim; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
A foundation is a non-profit legal entity with a strategic role in the social, educational, and humanitarian fields. The existence of foundation assets is the main backbone in ensuring the continuity of its activities. However, practices in the field show various problems such as misuse of assets, non-transparent management, and weak supervision and legal protection of these assets. This study aims to analyse the legal provisions in Law No. 28 of 2004 concerning Foundations, especially regarding asset protection and management, identify practices and challenges foundations face in managing their assets, and provide recommendations for improving relevant regulations and administration. This study uses a qualitative method with a normative and conceptual legal approach. Data sources were obtained from laws and regulations, legal literature, scientific journals, and case studies of foundation dissolution in Indonesia related to asset management. The analysis was carried out by reviewing the applicable legal provisions and reflecting them on factual practices in the field. The study results indicate that although Law No. 28 of 2004 has regulated the prohibition of profit sharing to foundation trustees, administrators, and supervisors, and stipulates provisions regarding the origin of assets and their use, there are still weaknesses in the implementation and supervision mechanisms. Several cases show irregularities by foundation administrators and weak legal protection for donors and beneficiaries. Therefore, there is a need for strengthening regulations, increasing transparency, and more effective supervision from the Ministry of Law and Human Rights and professional third parties. This study is expected to be an academic and practical contribution in improving the governance of foundation assets in Indonesia.Keywords: Foundation Assets; Protection; Management